Does ICT Use matter? How information and communication technology use affects perceived mattering among a predominantly female sample of older adults residing in retirement communities. Issue 9 (29th July 2019) - Francis, Jessica; Rikard, R. V.; Cotten, Shelia R.; Kadylak, Travis
ABSTRACT: Within the next 15 years, roughly 20% of individuals in the United States will be aged 65 years and older. As such, a significant portion of the population enters old age, it is imperative to understand the tools and mechanisms that may aid in the maintenance and improvement of older adults' well-being. Information and communication technologies (ICTs) are tools that may promote well-being through increased connectedness and reduction of isolation and depression. We suggest that ICT use may also enhance mattering, an individual's belief that they are important, acknowledged, and relied upon by others. This study examines the effect of ICT use on older adults' sense of mattering. Data were collected as part of a multi-site randomized controlled trial study. The aim of the study was to assess the effects of ICT training and use on older adults' quality of life and well-being. The sample included participants from 19 assisted and independent living communities. Results of our longitudinal and mediation analyses reveal that ICT use, through the promotion of social connectedness, has a significant and positive relationship with mattering. These results suggest that ICT use that facilitates connection and communication with social ties will be beneficial for enhancing well-being among older adults.